2017
DOI: 10.1002/dta.2206
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bleaching and coloring on ethyl glucuronide content in human hair

Abstract: Ethyl glucuronide (EtG) is increasingly used in forensic toxicology as a marker for alcohol use in analyses of hair samples, especially in abstinence control. Some cosmetic treatments are considered to markedly reduce the EtG content. In view of especially many women with coloured hair the present study was performed to further investigate the effect of a variety of colouring procedures (bleaching, tinting, permanent and semi-permanent dyeing, henna) on the EtG content.Untreated hair samples (n = 12, EtG 13.9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…Correlation of the EtG decrease (data in Petzel‐Witt et al) with the PTCA increase using the Spearman's rank correlation test was not significant (Spearman's rho = 0.248, p = 0.056). After excluding data of hair samples treated with henna and tinting, which exhibited PTCA contents that were not different from those of untreated hair, the correlation was also not significant (Spearman's rho = 0.238, p = 0.162).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Correlation of the EtG decrease (data in Petzel‐Witt et al) with the PTCA increase using the Spearman's rank correlation test was not significant (Spearman's rho = 0.248, p = 0.056). After excluding data of hair samples treated with henna and tinting, which exhibited PTCA contents that were not different from those of untreated hair, the correlation was also not significant (Spearman's rho = 0.238, p = 0.162).…”
Section: Resultsmentioning
confidence: 89%
“…The 12 natural hair samples used in a previous study exhibited PTCA contents of 7.6 ± 4.7 ng/mg (mean ± SD, range < 2.1–16.4 ng/mg). After cosmetic treatment with hair coloring products, the PTCA content (Table ) significantly increased for semi‐permanent dyeing (13.6 ± 8.2 ng/mg, p = 0.045), permanent dyeing (26.5 ± 13.8 ng/mg, p < 0.01) and for bleaching (41.1 ± 17.1 ng/mg, p < 0.001).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…2 The applications of EtG determination in hair range from compliance to driving regulation 3 to workplace testing 4,5 and many other usages of clinical and forensic interest. However, several studies have shown that bias can be induced by cosmetic treatments 13 exposure to chlorinated water, 14 external contamination by EtG-containing lotions, 15 and many others. [7][8][9] In practice, the effectiveness of EtG determination in hair as a biomarker for chronic excessive alcohol consumption outperforms all the other alcohol biomarkers [10][11][12] to the extent that is frequently used as a unique laboratory testing.…”
Section: Introductionmentioning
confidence: 99%